The Burdens of Survivorship: An Approach to Thinking about Long-Term Outcomes after Critical Illness - Iwashyna, Theodore J.; Netzer, Giora (Seminars in Respiratory and Critical Care Medicine, 2012)
Internationally accepted approaches to the study of functioning and disability can inform critical care practitioners and scholars in their study of functional limitations, disability, and quality of life after critical illness and intensive care. Therefore this article provides an introduction to the World Health Organization's International Classification of Functioning, Disability and Health (ICF). The Institute of Medicine has also recommended this approach for the study of disability. This conceptual framework divides potential problems as follows: problems in body structure and tissue, limitations in activity (i.e., functional limitations as assessed in standardized environments), and restrictions in participation (i.e., the inability to fulfill a social role). The ICF draws attention to effect modifiers that can prevent problems at one level from progressing (or conversely can hasten their progression) to profound decrements in a patient's quality of life. It is particularly relevant for studies of long-term outcomes after critical illness and post–intensive care syndrome (PICS). This article provides a discussion of the ICF specific to the intensive care unit and the disablement process, with particular attention to new opportunities for intervention and their implications for cost and quality of life.
Keywords: critical illness; post–intensive care syndrome (PICS); survivorship; disability; quality of life